All India Police Duty Meet Website (A) - Singla, Chitra; Singh, Bulbul, 1942- (London : Indian Institute of Management, Ahmedabad, 2020)
Madan Mohanka (MM) set up Tega Industries Ltd in 1976 to manufacture mill-lining products made from abrasion-resistant rubber for use in the mining and mineral-processing industries. This technology was completely new in India; MM had set up a plant for mill liners even before there were any takers for his products in the market. Tega first set foot in overseas markets in 1998 after becoming free from the export restraint that had been imposed on it by its mentor and stakeholder, Skega AB, a Swedish company. Tega received its first international order from Ghana and subsequently set up a sales subsidiary in the country. It then gradually opened sales and distribution offices in Australia, the USA, Mexico, and Canada. The business was slow to develop in each of these countries, and sales picked up after a tenuous ride. In 2006, as part of its inorganic expansion strategy, Tega bought a small rubber-manufacturing company that sold mill liners in South Africa. Between 2006 and 2011, Tega's business grew at a compound annual growth rate of 40%. Buoyed by this growth, Tega made two back-to-back acquisitions in Australia and Chile in 2011. However, several managerial, legal, and commercial problems crept up in its Chilean manufacturing facilities after the acquisition. These problems led to a severe financial downturn in Tega's fortunes in 2016, compelling it to either plan a revival or divest its interest in its Chilean plant.
Description based on XML content.
Keywords: elektronické knihy; electronic books; Globalization -- India -- Case studies; International business enterprises -- India; Corporate divestiture